2014
DOI: 10.1007/s10443-013-9370-3
|View full text |Cite
|
Sign up to set email alerts
|

Holistic and Consistent Design Process for Hollow Structures Based on Braided Textiles and RTM

Abstract: The present paper elaborates a holistic and consistent design process for 2D braided composites in conjunction with Resin Transfer Moulding (RTM). These technologies allow a cost-effective production of composites due to their high degree of automation. Literature can be found that deals with specific tasks of the respective technologies but there is no work available that embraces the complete process chain. Therefore, an overall design process is developed within the present paper. It is based on a correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Potluri et al proposed a linear design strategy, where the modeling is done in roughly the same order as the physical production [7]. Gn€ adinger et al showed the mutual dependencies of the various design features while striving for virtual design process chain integration [78]. They also showed the lack of integration of braiding process modeling and downstream resin infusion process modeling.…”
Section: Challengesmentioning
confidence: 99%
“…Potluri et al proposed a linear design strategy, where the modeling is done in roughly the same order as the physical production [7]. Gn€ adinger et al showed the mutual dependencies of the various design features while striving for virtual design process chain integration [78]. They also showed the lack of integration of braiding process modeling and downstream resin infusion process modeling.…”
Section: Challengesmentioning
confidence: 99%
“…It should be noticed that most studies focused on composite structure with constant or regular cross‐section profiles, whereas few studies were conducted on hollow composite structure with complex and variable cross‐section profile. With increasing requirements for structural efficiency in marine and aircraft applications, composite products with variable cross‐section are increasingly used , and thermal expansion process is a good choice for integral forming of such structure. For composite structure with constant cross‐section, the shape of core mold is regular and uniform thermal expansion of core mold is generally obtained at each region, resulting in uniform compaction pressure distribution on composite.…”
Section: Introductionmentioning
confidence: 99%